Personal thoughts of IgA nephropathy and purpura nephritis in children - Zhang Hong-wen (Linchuang shenzangbing zazhi)
IgA nephropathy （IgAN） and Henoch Schonlein purpura nephritis （HSPN） are common primary and secondary glomerular diseases in children.Renal manifestations， pathological findings and treatments of both diseases are rather similar.Based upon personal clinical experiences， the author proposed some personal thoughts on diagnostic criteria， clinical classifications， renal pathology and treatments of hematuria and proteinuria for IgAN and HSPN.It was intended only for peer discussions and references.